Difunctional monomeric and polymeric photoinitiators: synthesis and photopolymerization behaviors - Cesur, Belgin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
The first methacrylate monomers with two Type I or Type II side-chain photoinitiating groups (PI1, PI2 and PI3) have been synthesized from reactions of 2-(chloromethyl)acryloyl chloride and 4-hyroxybenzophenone, 4-hydroxyacetophenone or 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (Irgacure 2959) and polymerized to give the corresponding polymeric photoinitiators (PPI1, PPI2 and PPI3). The photoinitiator PI1 has also been copolymerized with N,N-dimethylaminoethyl methacrylate (DMAEM) to investigate the photoinitiation efficiency of the resulting polymer featuring built-in amine coinitiator. The photoinitiating activities of the synthesized photoinitiators together with acetophenone (AP), benzophenone (BP) and Irgacure 2959 were investigated in the photopolymerizations of hexane-1,6-diol diacrylate (HDDA) using photodifferential scanning calorimeter and the kinetic parameters have been correlated with the structures of the photoinitiating systems. The results show different photoinitiating activities compared to small molecule commercial analogs: BP-based photoinitiators, PI1, PPI1 and PPI(PI1-co-DMAEM), were found to be particularly efficient compared to BP. The difunctional nature of these photoinitiators suggests the possibility (demonstrated for PI3) of synthesizing crosslinked copolymers even with monofunctional monomers.
Keywords: Monomers.; Polymers.